Using a Moodle-based platform for online assessment during the COVID-19 pandemic: expectations vs reality - Ismawi, Hidayatul Radziah; Abd. Rahim, Nour El Huda; Khaing, Aye Thi; Mohamed Bakrim, Norbaiyah; Wan Omar, Wan Fatein Nabeila; Ismail, Soraya; Mohd Radzuan, Hazulin; Mat Harun, Noraihan; Mohd Noor, Mohd Fadly; Abdul Rahim, Roslina; Mohd Zainudin, Maizura; Hamzah, Hairul Aini; et al. (2020)
INTRODUCTION: The implementation of the Movement Control Order (MCO) due to the global pandemic caused by COVID-19 resulted in the activation of Emergency Remote Teaching and Learning (ERTL) at the Department of Basic Medical Sciences, Faculty of Medicine, International Islamic University Malaysia since conventional face to face teaching was no longer an option. Student assessment methods needed to be designed and implemented using the university provided Moodle based e-learning system (ELS) known as iTa’LeEm for use during ERTL. OBJECTIVE: This study aimed to determine the perceived and actual lecturer’s experiences when using iTa’LeEm as an online student assessment tool. Feedback was received from 14 lecturers involved in the newly formed Exam Unit. The questionnaire consisted of a 5-point Likert scale as well as qualitative questions regarding the lecturer’s perceptions of the information quality, system quality, perceived usefulness and user satisfaction of the chosen online assessment method before and after the implementation of ERTL. RESULTS: From the feedback, the majority of lecturers had low perceptions of the accuracy, reliability and completeness of iTa’LeEm prior to usage but the scores drastically increased after implementation of iTa’LeEm for online student assessment. Many lecturers also doubted the system easiness, responsiveness and stability in use prior to implementation and their perception differed greatly after ERTL. Opinions regarding the perceived usefulness of iTa’LeEm and user satisfaction were low prior to ERTL but greatly improved after implementation. From the feedback, the initial main concerns among lecturers was regarding technical aspects such as connection issues and student access to devices however post ERTL the majority of concerns centred around student integrity and comprehensiveness of the exam. DISCUSSION: The study provided objective insight into the difference between perceived and actual experience when implementing an established assessment tool in a novel setting. CONCLUSION: Although the implementation of iTa’LeEm Moodle based e-learning system as an online assessment tool was due to unplanned circumstances, it provided an opportunity for lecturers to familiarise themselves with a good university provided online assessment system that can be used as an alternative method of assessment even after ERTL.